Innovative projects in conditions of innovative development of Kazakhstan Republic (Journal of Economic Research & Business Administration, 2015)
The main considered moments are: amount of the state support of innovative projects on the near-term outlook, through what programs support is realizing, main supporting structures of innovative development, weaknesses of the support realization, and in what aspects it is necessary to focus. Relevance of development of economy in an innovative context is transmitted through the Message of the President of the Kazakhstan Republic N. Nazarbayev to the people of Kazakhstan (of January 17, 2014). Importance of selection of perspective innovative projects, and involvement of foreign experts is described. Considering the actual directions of development of innovations which will help domestic economy to receive high return on the basis of use of direct investments and application of foreign trade, tax and otherinstruments of the state regulation, capable to provide production of new competitive types of production are: space, new power industry, biotechnologies, special chemistry, telecommunications and communication. Also at work there is a statistical review: innovative activity of the enterprises in RK, an orientation of investments in innovative sector, an average monthly salary of the personnel occupied with researches and development.
Keywords: innovative projects; costs of innovations; innovative activity; support of innovations; selection of projects